2015
DOI: 10.1155/2015/105172
|View full text |Cite
|
Sign up to set email alerts
|

Neural Differentiation of Human Pluripotent Stem Cells for Nontherapeutic Applications: Toxicology, Pharmacology, andIn VitroDisease Modeling

Abstract: Human pluripotent stem cells (hPSCs) derived from either blastocyst stage embryos (hESCs) or reprogrammed somatic cells (iPSCs) can provide an abundant source of human neuronal lineages that were previously sourced from human cadavers, abortuses, and discarded surgical waste. In addition to the well-known potential therapeutic application of these cells in regenerative medicine, these are also various promising nontherapeutic applications in toxicological and pharmacological screening of neuroactive compounds,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 112 publications
0
28
0
1
Order By: Relevance
“…Publications with human NPCs started to demonstrate their use in assessing toxicological profile of drugs [25,27]. Using hESC-derived NPCs, a research group described a platform for detection of toxicity to neuronal induction in embryonic development [28].…”
Section: The Current State-of-the-art Of Using Hpsc For Cns Safety Scmentioning
confidence: 99%
“…Publications with human NPCs started to demonstrate their use in assessing toxicological profile of drugs [25,27]. Using hESC-derived NPCs, a research group described a platform for detection of toxicity to neuronal induction in embryonic development [28].…”
Section: The Current State-of-the-art Of Using Hpsc For Cns Safety Scmentioning
confidence: 99%
“…The DPSCs promoted the regeneration of transacted axons by directly inhibiting multiple axon growth inhibitors and by prevention of apoptosis of neurons, astrocytes and oligodendrocytes. The DPSCs were then differentiated into mature oligodendrocytes to replace the cells that were lost (16,37,38,39,40).…”
Section: Neural Differentiationmentioning
confidence: 99%
“…DPSCs has also shown to be differentiated into cells with morphological, phenotype and functional characteristics similar to hepatocytes. It has been further suggested that the stem cells derived have the capacity to differentiate into hepatic family (37,38).…”
Section: Differentiation To Hepatocytementioning
confidence: 99%
“…Further, the in vitro neural differentiation of PSCs recapitulates in vivo neural development (Abranches et al, 2009;Mertens et al, 2016), thereby making these cells a suitable model for neurodevelopmental studies. PSC-derived neural cells have been employed for toxicological studies, disease modeling, and drug screening (Avior et al, 2016;Marchetto et al, 2011;Yap et al, 2015). Most importantly, PSCs serve as an excellent source of cells for potential cell replacement for the treatment of various neurodegenerative diseases and disorders http://dx.doi.org/10.1016/j.ijdevneu.2017.06.009 Received 26 May 2017; Received in revised form 13 June 2017; Accepted 29 June 2017 (Jongkamonwiwat and Noisa, 2013).…”
Section: Introductionmentioning
confidence: 99%